Exploring the biological activity and setting dynamics of a novel polydopamine-based root repair material - Lakshmi Nidhi Rao; Aditya Shetty; Arun M. Isloor; Sooraj Nayak; Mohana Kumar; Jayaprakasha Shetty K; Muttanna Venkatesh (Journal of Oral Biology and Craniofacial Research)
Background: Root perforation represents a significant complication in endodontics, compromising the structural integrity of the tooth. Effective repair are critical to mitigating the associated risks and preserving long-term dental function. Despite extensive research, the ideal repair material that fulfills all requisite biological and mechanical properties remains elusive. Methodology: This study introduces a novel polydopamine based repair material designed to address the limitations of existing materials. The material was characterized using field emission scanning electron microscopy, X-ray diffraction, Fourier-transform infrared spectroscopy, transmission electron microscopy, zeta potential, and particle size analysis. The material's initial and final setting times were evaluated using a Gilmore needle apparatus. Biocompatibility was assessed via the MTT assay, while bioactivity was quantified through calcium ion release analysis. Comparative evaluations were conducted against ProRoot MTA, a commercially available standard in root repair. Results: The findings revealed no statistically significant differences in cytotoxicity (P > 0.05) between the experimental material and ProRoot MTA, affirming the biocompatibility of both. However, the experimental material demonstrated a significantly faster set (P < 0.001) than ProRoot MTA, a critical advantage in clinical applications. the inclusion of calcium chloride and bioactive glass enhanced calcium ion release, with the experimental material showing significantly higher levels at 7 days. Conclusion: The polydopamine-bioactive glass composite exhibited favorable biological activity, superior setting dynamics, and enhanced bioactivity, positioning it as a promising candidate for perforation repair. These results lay the groundwork for further research and potential clinical translation, offering a viable solution to a longstanding challenge in endodontics.